Convergence of Celebrity Culture and Citizen Journalism: Analysis of Journalism Practice in Nigeria - Ololade Olatunji Lateef (Lakhomi Journal Scientific Journal of Culture, 2025)
The convergence of celebrity culture and citizen journalism has dramatically reshaped the landscape of journalism practice in Nigeria. This study explores how the fusion of these two influential forces has redefined traditional journalistic norms, altered content production, and challenged established media hierarchies. With celebrities increasingly acting as news sources and even content creators, and citizens leveraging digital platforms to disseminate information, often unfiltered and real-time, the boundaries between professional journalism, entertainment, and user-generated content have become increasingly blurred. Using constructivism philosophy of research design and in-depth interview method, this study examines celebrity culture and citizen journalism within the context of journalism practice in Nigeria. The study adopted The Social Responsibility Theory of the Press. The study adopted in-depth interview while 5 senior editors from each newspaper were selected for the in-depth interview. Purposive sampling was employed to select the participants. Data was collected through face-to-face interviews, Zoom, and email, with interviews lasting between 45 and 60 minutes. The interviews were recorded and transcribed for analysis. The guide for in-depth interviews included open-ended questions that explored journalists' experiences with celebrity culture. NVivo was used to analyse the in-depth interview using thematic analysis. The findings reveal that while this intersection offers new opportunities for democratized storytelling and wider engagement, it also raises concerns about misinformation, credibility, and the dilution of journalistic integrity. The study concludes by calling for a reimagining of media ethics and professional training to adapt to a rapidly evolving digital media ecosystem shaped by the dual influence of celebrity culture and citizen participation.